An Institutional Explanation for Economists' Theoretical and Methodological Choices. Issue 1 (2nd January 2017) - Almeida, Felipe; Angeli, Eduardo; Pontes, Renato
ABSTRACT: Scientific research in general and economics research in particular is a social act. More specifically, schools of economic thought as well as associations, research groups and conferences are expressions of social organizations within the realm of economics. Historically, studies investigating the methodologies used in economics have focused on the strengths of these social organizations. This study aims to analyze the key roles played by individuals within social organizations in building and reinforcing economics and, in turn, their influence on these individuals. To achieve this goal, we use an institutionalist approach in a broad sense. We show how economics as an academic environment can be presented as an institutional entanglement and how an institutionalist approach can enhance an understanding of why economists adopt a particular theoretical and methodological perspective. It is argued that habits, observations and cognitive abilities should be seriously considered to understand the logic and decision making of economic researchers. We discuss also the importance of forming groups in the process of institutionalizing elements relevant to an economic researcher's logic and decision making and present an interpretation of mainstream economics in terms of the analytical approach of our study.